2015
DOI: 10.3390/photonics2030838
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Irregular Bimetallic Nanostructures on the Optical Properties of Photosystem I from Thermosynechococcus elongatus

Abstract: The fluorescence of photosystem I (PSI) trimers in proximity to bimetallic plasmonic nanostructures have been explored by single-molecule spectroscopy (SMS) at cryogenic temperature (1.6 K). PSI serves as a model for biological multichromophore-coupled systems with high potential for biotechnological applications. Plasmonic nanostructures are fabricated by thermal annealing of thin metallic films. The fluorescence of PSI has been intensified due to the coupling with plasmonic nanostructures. Enhancement factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Over a century, noble-metal nanostructures have attracted the scientific community because of their SPR with respect to visible light, since the discovery of interaction of light with spherical particles present in the air by Mie in 1908 . However, bimetallic NPs of noble metals, constituted of two different metals with core–shell structure and alloy nanostructures, have captured enormous attention because of their unique physical properties like optical, magnetic, electronic, and particularly chemical, catalytic properties, along with their diverse and wide range of applications in catalysis, photonics, surface enhanced Raman scattering (SERS), chemical and biological sensing, and electrochemical water splitting . These properties are distinctly superior to their homogeneous monometallic counterparts (constituted of single metal NPs), resulting from the synergistic effects of both metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Over a century, noble-metal nanostructures have attracted the scientific community because of their SPR with respect to visible light, since the discovery of interaction of light with spherical particles present in the air by Mie in 1908 . However, bimetallic NPs of noble metals, constituted of two different metals with core–shell structure and alloy nanostructures, have captured enormous attention because of their unique physical properties like optical, magnetic, electronic, and particularly chemical, catalytic properties, along with their diverse and wide range of applications in catalysis, photonics, surface enhanced Raman scattering (SERS), chemical and biological sensing, and electrochemical water splitting . These properties are distinctly superior to their homogeneous monometallic counterparts (constituted of single metal NPs), resulting from the synergistic effects of both metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of the interactions of gold or silver NPs with photosynthetic proteins have focussed in the main on the photophysical consequences, including enhanced absorption and energy transfer. [80][81][82][83][84][85][86][87][88][89][90][91][92] A smaller number of studies have reported the impact of plasmonic interactions on photocurrents from photosynthetic materials on electrodes or in cells. Enhancements have been seen after placing Photosystem I complexes on a silver island film 93 and decorating thylakoid membranes with gold nanorods.…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, few studies have systematically investigated spatially and spectrally resolved plasmonic tuning of the optoelectronic properties of a multichromophore supramolecular protein such as PSI (∼1068 kDa in weight). To this end, prior studies have shown that plasmonic nanoparticles can couple with the intrinsic light-harvesting antennae in PSI to enhance the absorption of PSI–nanoparticle hybrid systems. , Furthermore, it has also been shown that the fluorescence emission pathways and intensities in PSI can be significantly altered by plasmonic nanoparticles. Models of plasmon-enhanced excited electron generation in PSI can inform experimentally plausible strategies for enhanced photocurrent generation . Inspired by these studies, our recent work reported the first-ever experimental verification of plasmon-enhanced photocurrents from PSI assembled on Fischer nanopatterns of Ag nanopyramids (AgNPs) whose plasmon absorption peaks were tuned to the PSI absorption peaks at ∼440 and 680 nm .…”
Section: Introductionmentioning
confidence: 91%